Adverse Reactions Following Influenza Vaccination Among Health Care Personnel at Govt. Medical College, Miraj – A Longitudinal Study - Naik, Jayashree Dayanand; Rajderkar, S.S.; Patel, Kriti A; Jathar, Sanjay K (National Journal of Community Medicine, 2011)
Influenza continues to be a significant cause of morbidity and mortality globally. Health Care Personnel (HCP), the backbone of health care delivery system, have been identified as an important source of influenza for patients. Vaccination is a useful but underused means of preventing the illness and death associated with Influenza and the coverage is lower than expected among HCP. So, a longitudinal study to assess the frequency and pattern of adverse reactions following influenza vaccination among 130 HCP , participating voluntarily, was carried out at Govt. Medical College, Miraj and they were followed for the period of one year.71.5% of the study subjects had taken nasal type of vaccine . The overall incidence of adverse reactions after vaccination was 40%, commonly during first 3 days, with declining frequency over 1 week and the reactions were mild. None of the vaccinees reported severe adverse reactions.